Quantitative assessment of breast-tumor stiffness using shear-wave elastography histograms - Papageorgiou, Ismini E.; Valous, Nektarios A.; Hadjidemetriou, Stathis; Teichgräber, Ulf; Malich, Ansgar (Diagnostics, 2022)
Shear-wave elastography (SWE) measures tissue elasticity using ultrasound waves. This study proposes a histogram-based SWE analysis to improve breast malignancy detection.